Robot - Bridgman, Roger Francis, 1940-; Teague, Steve (London : DK, 2004)
Presents information on robots, in simple text with illustrations, looking at different types of robots, how they work, and how they are used.
Includes index.
Horn Book, October 2004.
Science Books & Films (A.A.A.S.), May 2004.
7.8
5-8
IG1050L
Keywords: Robots -- Juvenile literature; Robots; Robots; Robots